OXYGEN ISOTOPE SALT EFFECTS AT HIGH PRESSURE AND HIGH TEMPERATURE AND THE CALIBRATION OF OXYGEN ISOTOPE GEOTHERMOMETERS - Hu G.; Clayton R.N. (My University, 2003)
The influence of NaCl, CaCl2, and dissolved minerals on the oxygen isotope fractionation in mineral-water systems at high pressure and high temperature was studied experimentally. The salt effects of NaCl (up to 37 molal) and 5-molal CaCl2 on the oxygen isotope fractionation between quartz and water and between calcite and water were measured at 5 and 15 kbar at temperatures from 300 to 750°C. CaCl2 has a larger influence than NaCl on the isotopic fractionation between quartz and water. Although NaCl systematically changes the isotopic fractionation between quartz and water, it has no influence on the isotopic fractionation between calcite and water. This difference in the apparent oxygen isotope salt effects of NaCl must relate to the use of different minerals as reference phases. The term oxygen isotope salt effect is expanded here to encompass the effects of dissolved minerals on the fractionations between minerals and aqueous fluids. The oxygen isotope salt effects of dissolved quartz, calcite, and phlogopite at 15 kbar and 750°C were measured in the three-phase systems quartz-calcite-water and phlogopite-calcite-water. Under these conditions, the oxygen isotope salt effects of the three dissolved minerals range from ∼0.7 to 2.1‰. In both three-phase hydrothermal systems, the equilibrium fractionation factors between the pairs of minerals are the same as those obtained by anhydrous direct exchange between each pair of minerals, proving that the use of carbonate as exchange medium provides correct isotopic fractionations for a mineral pair.